Research Progress on Nutritional Components and Functional Characteristics of Sprouted Highland Barley - Yuting FAN; Kexin WANG; Haixia ZHANG; Ping MA; Jing LI; Jing WU; Youjin TAN; Jianbin WANG; Xiaoyan HE; Shuangkui DU (Shipin gongye ke-ji)
Highland barley, a distinctive and advantageous crop predominantly grown in the western plateau regions of China, boasts characteristics such as cold resistance, drought tolerance, strong adaptability, high yield, and early maturity. As a method to improve the utilization of nutrition and bioactive ingredients in plant seeds, germination has received increasing attention nowadays where public health awareness has generally improved. Sprouted highland barley is very promising in food and medicine related fields since it has both higher nutrition value and better biological activities comparing with raw highland barley. This paper summarizes the changes in nutrition components and functional constituents after highland barley sprouted. Germination increased the content of dietary fiber, various essential amino acids, ω-6 fatty acids, ω-3 fatty acids, vitamins, γ-aminobutyric acid and other ingredients effectively, while reducing the content of starch and fat. The research progress of the functional properties of sprouted highland barley, such as antioxidant, antibacterial, blood glucose regulation, blood pressure regulation, are mainly reviewed, in order to provide reference for the development and utilization of sprouted highland barley.